Pengaruh Human, Organization dan Technology (Hot) Terhadap Kualitas Iinformasi Pelaporan Keuangan Pada Badan Layanan Umum - Siti Amerieska (Akutansi Bisnis & Manajemen ( ABM ), 2016)
This study pupose to examine the human (human resource capacity), organization (application of accounting standards and internal control systems) and technology towads the quality of financial reporting information in Badan Layanan Umum (BLU). The population of this study are all users who carry out financial reporting. Data used in this study are primary data, which obtained from distributing questionnaires. The results of this study that simultaneously signify the human variables, technology significantly influence the quality of financial reporting information Badan Layanan Umum (BLU). While variable implementation of standards accounting does not have a significant effect, but for variable application of the system of internal control has significant effect.